On Populist Illusion: Impasses of Political Ontology, or how the Ordinary Matters - Vega, Facundo Hernan (2021)
Amplifying the distinction between ‘politics’ and ‘the political’, Ernesto Laclau crowns his examination of the blind spots of the Marxist tradition with an encomium of populism. His project to recentre ‘the political’ does not postulate a beginning marked by a great event. Instead, Laclau celebrates ontological foundation as the abyss of all politicity. This chapter critically assesses how Laclau invests the body of the populist leader with an extra-quotidian character. I will also show how the assumption that the body of the leader animates political beginnings and primordially channels them restrains Laclau’s previous ‘deepening of the materialist project’.